Effects of Sleep Pattern, Stress, Menstrual Attitude, and Behavior That Reduces Exposure to Endocrine Disrupting Chemicals on Premenstrual Syndrome in Adolescents - Hye Jin Kim; So Young Choi; Haeyoung Min (Korean Society of Women Health Nursing, 2019)
PURPOSE: The study aimed to examine the effects of sleep pattern, stress, and attitude towards menstruation, and behavior that causes a reduction in exposure to endocrine disrupting chemicals (EDCs) in the course of premenstrual syndrome (PMS) in female adolescents. METHOD: In total, 200 girls attending middle school in K city were recruited via convenience sampling between December 11 and 31, 2018, and 192 subjects were selected for the analysis. Data were analyzed using descriptive statistics, an independent t-test, ANOVA, Pearson's correlation coefficient, and multiple regression. RESULTS: Overall, 9 (4.7%), 152 (79.2%), and 31 (16.1%) students had morning-, intermediate-, and evening-type sleep pattern, respectively. The mean scores for school-related stress were highest. Scores for stress regarding relationships with friends were the lowest. The mean score for attitudes toward menstruation was 72.33 out of 147. The mean score for behavior that led to a reduction in EDCs exposure was 56.57 out of 85. The mean scores for PMS severity were 25.30 and 38.39 out of 60. Analysis of factors affecting PMS revealed that severity of menstrual pain (β=.28), use of analgesics during menstruation (β=.17), family history of PMS (β=−.16), stress (β=.19), and behavior that reduces EDCs exposure (β=−.17) exerted significant effects on PMS. The explanatory power of these variables was 37%. CONCLUSION: The findings propose the necessity of a health intervention program including educational information, which can reduce PMS in adolescents, induce the behaviors which can decrease exposure to EDCs, and activities for managing the stress levels.